A framework for recognizing diversity beyond capitalism in agri-food systems. (December 2020) - Koretskaya, Olga; Feola, Giuseppe
Abstract: Calls for agri-food system sustainability transitions abound and increasingly draw attention to the need for addressing deeply ingrained social, cultural and economic logics that drive unsustainability, and specifically political economy of the systems of provision. Yet, the analytical conceptualization of diversity with regards to capitalism in agri-food systems remains limited. This paper fills this gap by proposing and illustrating a framework for recognizing capitalist, alternative capitalist, and non-capitalist configurations in enterprises, cooperatives, associations, and other socioeconomic entities in agri-food systems. The framework is informed by poststructuralist theories of capitalism and development, as well as by other analyses and critiques of capitalism rooted in relational understandings of society-in-nature. It entails the following dimensions: (a) ontology: space, time, human nature, logic of relation; (b) economic relations: enterprise, labour, economic transactions, Property, finance; (c) relation with the State: participation in regulation and legitimation; (d) knowledge. The application of the framework to cases of community supported agriculture (CSA) shows the coexistence of capitalist, alternative-capitalist or non-capitalist elements in CSA initiatives. Distinct CSA initiatives show different configurations of the framework's elements. In some cases, configurations changed over time as a result of tensions between actors, or between the CSA and its context. The uncovering of these dynamics proves that the framework can be a valuable tool for recognizing diversity beyond capitalism in a given food initiative. Highlights: Framework for recognizing more-than-capitalist configurations in agri-food systems. Extends existing frameworks of economic diversity, and broadens the discussion on the dimensions of difference. Framework entails four dimensions: ontology, economic relations, relation with the State, knowledge. Application to Community Supported Agriculture proves that the framework helps recognizing diversity beyond capitalism.